217k views
0 votes
Given f(x)=x^3-2, find the equation of the secant line passing through (-4,f(-4)) and (2,f(2))

User Kms
by
4.9k points

1 Answer

9 votes

Given:

The function is


f(x)=x^3-2

The secant line passing through (-4,f(-4)) and (2,f(2)).

To find:

The equation of the secant line.

Solution:

We have,


f(x)=x^3-2

At x=-4,


f(-4)=(-4)^3-2


f(-4)=-64-2


f(-4)=-66

At x=2,


f(2)=(2)^3-2


f(2)=8-2


f(2)=6

The secant line passes through the points (-4,-66) and (2,6). So, the equation of the secant line is


y-y_1=(y_2-y_1)/(x_2-x_1)(x-x_1)


y-(-66)=(6-(-66))/(2-(-4))(x-(-4))


y+66=(6+66)/(2+4)(x+4)


y+66=(72)/(6)(x+4)

On further simplification, we get


y+66=12(x+4)


y+66=12x+48


y=12x+48-66


y=12x-18

Therefor, the equation of the secant line is
y=12x-18.

User Cjk
by
5.2k points